BENTHIC FORAMINIFERAL ASSEMBLAGES IN NATUNA ISLANDS - Suhartati M. Natsir; M. Subkhan; Rubiman Rubiman; Singgih P.A. Wibowo (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
Natuna Islands cluster consisting of large and small islands which a very diverse ecosystems are occurred, including mangrove, seagrass and coral reefs. These waters can be a conducive habitat for various marine organisms, including foraminifera that can live in all types of waters. Collected foraminifera from a site reflect the relationships between species that are affected by ecological factors and the ability of these organisms adapt to their environment. These organisms are also used in the petroleum and mining line, and studied in the micropaleontology and palaeoecology. Therefore, the data on foraminifera in a marine community, including the waters of Natuna Islands are very important to support the fields. Sampling of this study was conducted in April 2011 in the waters off the coast until the ocean waters covering Bunguran, Subi Besar and Laut Islands. The benthic foraminifera that was collected as abundant in these three waters is symbiont bearing foraminifera, namely Amphistegina lessonii.Keywords: Assemblage, foraminifera, benthic and Natuna